The Effect of Using an AI-Based Adaptive Learning Platform on Improving Students' Mathematics Learning Outcomes - Reno Purnomo; Sovian Sauri; Tomi Ariq; Salwa Rania (Gema Cendekia Institute, 2025)
This research investigates the impact of using AI-based adaptive learning platforms on improving student learning outcomes in Computer Networks at SMK Negeri 2 Mataram. The study is prompted by the rapid advancements in information and communication technology, which have led to the integration of AI in education, particularly in adaptive learning platforms that can tailor learning materials and methods to individual student needs. Initial observations at SMK Negeri 2 Mataram revealed limited use of AI-based learning, resulting in students being passive with conventional teaching methods. This descriptive qualitative research was conducted in the even semester of the 2024/2025 academic year at SMK Negeri 2 Mataram. The subjects included Computer Networks teachers and 10 tenth-grade students. Data were collected through semi-structured interviews, essay tests, and documentation, then analyzed by data reduction, data presentation, and conclusion drawing. The findings reveal an interesting paradox. Although the school administration and teachers still restrict AI usage due to concerns about student dependency and a decline in critical thinking skills, experimental essay test results showed a significant improvement in the quality of student answers when AI was utilized. Responses became more comprehensive, structured, and demonstrated a deeper understanding of concepts. This suggests that AI can serve as an effective tool to enhance comprehension and boost student motivation. However, it is crucial to balance AI integration with the development of AI literacy and an emphasis on independent learning, ensuring students use this technology wisely as a support, not a replacement for their own thinking processes.